Pola Interaksi Edukasi dalam Genelogy Tradisi Keilmuan Jami'al-Azhar - Zulfahmi Syamsuddin; Asyraf Isyraqi Jamil; Fakhrul Adabi Abdul Kadir (At-Tafkir, 2021)
This article discusses Jami 'al-Azhar as a center for the knowledge study and the holistic interaction of teacher-student relationships. On the other hand, the position of teachers continues to be marginalized in the digital era. Hence, it is pivotal to look back at the teacher-student relationship that has prevailed in the history of Islamic education, especially in Jami 'al-Azhar. The research methodology employed literature review with a historical approach through primary and secondary source analysis. This study found that Jami 'al-Azhar was a center for the Islamic studies and study of science, initially aimed as propaganda for the Kingdom of Fathimiyah to perpetuate Shi'i understanding. However, the rank continued to develop to give a role as a center of thought and knowledge that gave birth to scholars from various schools of thought. One of its uniqueness as a center for the study of science is to perpetuate the interaction of teacher-student relationships in various traditions. Among the most prominent traditions are sanad, ijazah, suhbah, and talaqqi. Therefore, it can be concluded that the practice of teaching at Jami 'al-Azhar is manifested through the knowledge geneology and mentor system